THE INFLUENCE OF LIVE SHOPPING, DISCOUNTS, AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS ON SHOPEE - Wibowo, M. Chandra (JAMBURA: Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study examines the extent to which live shopping, price discounts, and product quality influence consumer purchase decisions within the Shopee platform. A quantitative approach was employed using a causal research design, with data analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The sample consisted of 185 respondents selected through purposive sampling, specifically individuals with prior experience purchasing via Shopee’s live shopping feature. Data were collected using a structured questionnaire with a Likert scale. The results reveal that all three variables significantly and positively affect purchase decisions, with path coefficients of 0.519 (live shopping), 0.391 (discounts), and 0.465 (product quality) (p 0.05). Among these, live shopping demonstrates the strongest influence. The model explains 68.8% of the variance in purchase decisions (R² = 0.688), indicating strong predictive capability. These findings suggest that consumer decisions in digital commerce are increasingly shaped by interactive and experiential factors alongside traditional economic considerations.